Hydrogen radical-boosted electrocatalytic CO2 reduction using Ni-partnered heteroatomic pairs - Zhibo Yao; Hao Cheng; Yifei Xu; Xinyu Zhan; Song Hong; Xinyi Tan; Tai-Sing Wu; Pei Xiong; Yun-Liang Soo; Molly Meng-Jung Li; Leiduan Hao; Liang Xu; et al. (Nature Communications)
Abstract The electrocatalytic reduction of CO2 to CO is slowed by the energy cost of the hydrogenation step that yields adsorbed *COOH intermediate. Here, we report a hydrogen radical (H•)-transfer mechanism that aids this hydrogenation step, enabled by constructing Ni-partnered hetero-diatomic pairs, and thereby greatly enhancing CO2-to-CO conversion kinetics. The partner metal to the Ni (denoted as M) catalyzes the Volmer step of the water/proton reduction to generate adsorbed *H, turning to H•, which reduces CO2 to carboxyl radicals (•COOH). The Ni partner then subsequently adsorbs the •COOH in an exothermic reaction, negating the usual high energy-penalty for the electrochemical hydrogenation of CO2. Tuning the H adsorption strength of the M site (with Cd, Pt, or Pd) allows for the optimization of H• formation, culminating in a markedly improved CO2 reduction rate toward CO production, offering 97.1% faradaic efficiency (FE) in aqueous electrolyte and up to 100.0% FE in an ionic liquid solution.